1988
DOI: 10.1007/bf01311072
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for more than one important, neutralizing site on foot-and-mouth disease virus

Abstract: Using polyclonal sera raised against foot-and-mouth disease virus in susceptible animals, evidence was obtained for the existence of at least one further important antigenic site in addition to the neutralizing site on VP1 140-160.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…MAbs have been used extensively to identify several antigenic sites on the structural proteins of virions belonging to serotypes A (15)(16)(17), O (13,18), C (19), and Asia-1 (20). Not surprisingly, these antigenic sites were located on structural protrusions on the virus surface, formed mainly by the loops connecting ␤-barrel structures of the three outer capsid proteins.…”
mentioning
confidence: 99%
“…MAbs have been used extensively to identify several antigenic sites on the structural proteins of virions belonging to serotypes A (15)(16)(17), O (13,18), C (19), and Asia-1 (20). Not surprisingly, these antigenic sites were located on structural protrusions on the virus surface, formed mainly by the loops connecting ␤-barrel structures of the three outer capsid proteins.…”
mentioning
confidence: 99%
“…This was supported by the fact that animals with low levels of neutralizing antibodies could also be protected [34-37]. A broad repertoire of epitope specificities following vaccination has been observed in previous studies [38,39]. Also, Nagendrakumar [33] have reported that the hyperimmune sera collected from vaccinated animals were unable to compete with the panel of mAbs used in their study.…”
Section: Discussionmentioning
confidence: 69%
“…However, a potential problem with this approach is that antibody bound to one site may interfere with a competitive ligand targeted elsewhere on the virus surface, due to the small size of the virion and close vicinity of different antigenic sites. Other studies involving serotype C (Mateu et al , 1995) and serotype A (Thomas et al , 1988b) also indicated the participation of other antigenic sites in addition to site 1 in generation of an immune response following either natural infection or vaccination.…”
Section: Full Textmentioning
confidence: 98%